Leptospirosis in Malaysia - an overview. - Bahaman, Abdul Rani (1989)
This paper attempts to provide an overall account of leptospirosis in Malaysia. Fletcher (1928) provided a detailed description of the disease as seen in Malaysia and is the foundation for further studies in this field in this country. Subsequent investigations were mainly on the description and diagnosis of the disease, particularly from the human and wildlife aspects. Pyrexia of unknown origin (PUO) in civilians and military personnel were frequently reported and a large number (28%) of the cases were suspected to be due to leptospirosis. Recent reports indicated high prevalence of a leptospiral infection in cattle, buffaloes and pigs whilst sporadic infection was seen in sheep and goats. The vast number of leptospiral serovars that have been reported in the country, the abundance of maintenance hosts and conducive climate and environment would generate ample materials for research in this field. Investigations on the economic, epidemiology and public health aspects of the disease are lacking and therefore warrant further investigation.